PERENCANAAN CHECKDAM KALI NGASINAN KANAN DESA NOTOREJO KECAMATAN GONDANG KABUPATEN TULUNGAGUNG - Ahmad Nashirudin; Sigit Winarto; Sudjati Sudjati (Faculty of Engineering, Kadiri University, 2018)
Checkdam is a controlling building created because of the flow of water with a large enough sediment concentration, where the sediment comes from soil erosion in the upstream part of the river, to find out the analysis of hydrology, regarding its rainfall, analyze the flood discharge. With the form of a checkpoint in the village of Notorejo, it can prevent and reduce disasters due to the flow of sediments that are formulated in such a way that the river concerned can function normally and effectively in terms of two angles, namely flood control and river development. Rainfall based on calculation of log pearson type III on R20 is 100mm, and Flood Debit Plan 167 m3 / dt. The ability of the sediment capacity of 700,692 m3 / dt and the capacity of sediment capacity to remain 525,519. and able to withstand shear force and rolling stability, this discharge plan is useful for reducing sediment that enters the river salts and provides safety of surrounding agricultural areas due to erosion, stabilizes the riverbed, directs river flow and reduces the occurrence of breakdowns in bridge structures along the river flow mate. Checkdam adalah bangunan pengendali yang dibuat karena adanya aliran air dengan konsentrasi sediment yang cukup besar, dimana sedimen tersebut berasal dari erosi tanah pada bagian hulu sungai, Untuk mengetahui tinjauan analisa hidroliginya, mengenai curah hujannya, analisa debit banjirnya. Dengan di bentuknya cekdam di desa notorejo dapat mencegah dan mengurangi bencana akibat aliran sedimen yang dirumuskan sedemikian rupa sehingga sungai yang bersangkutan dapat berfungsi normal dan efektif di tinjau dari dua sudut yaitu pengendalian banjir dan pengembangan sungai. Curah hujan berdasarkan perhitungan log pearson type III pada R20 adalah 100mm, dan Debit Banjir Rencana 167 m3/dt. Kemampuan daya tampung sedimen 700.692 m3/dt dan kemampuan daya tampung sedimen tetap 525.519. dan mampu menahan stabilitas gaya geser dan guling,debit rencana ini bermanfaat untuk mengurangi sedimen yang masuk ke checkdam kali ngasinan dan memberikan pengamanan daerah pertanian di sekitar akibat erosi, menstabilkan dasar sungai, mengarahkan aliran sungai dan mengurangi timbulnya kerobohan pada struktur jembatan di sepanjang aliran sungai ngasinan.